The Role of Public Relations in Successful Organizational Management - Ghorzang, Sabghatullah (IJRDO - Journal of Social Science and Humanities Research, 2021)
In recent years, public relations in every organization have become an integral part of the management team, especially in western countries, but in Asian countries currently, public relations are a developing part of an organization. Public relations people work for government agencies, businesses, professional and trade associations, nonprofit charities, universities, schools, hospitals, hotels, and finally for every organization everywhere, nowadays public relations is the inseparable part of successful organizational management.        Consequently, professionals and experts of communication and management and also business workers alike have looked for the key concept to establish the value of public relations. As a respect, the terms of relationships and reputation have emerged as the focal concepts in defining the purpose and value of public relations. The concept of organization-public relationship and organizational reputation can be integrated within a theoretical framework of public relations effectiveness; furthermore, this study examines the role of public relations in successful organizational management and describing organizational functions of public relations, the organizational functions of public relations comprise multiple specialties designed to help a company manage its relationships with key stakeholders, for instance, internal relations practitioners, investor relations practitioners, media relations specialists, government relations specialists, and research specialists. As well as this paper arguing that, Public relations as a management function.